A conceptual model for simulating responses of freshwater macroinvertebrate assemblages to multiple stressors. (October 2020) - de Vries, Jip; Kraak, Michiel H.S.; Verdonschot, Piet F.M.
Graphical abstract: Highlights: Requirements for models simulating macroinvertebrate responses were formulated. A model that includes stressor interactions and reports uncertainties is needed. Ideally, stressors acting on multiple spatial and temporal scales are represented. A conceptual model consisting of selected building blocks of existing models was described. Application of the final model may help to focus restoration practices. Abstract: Simulating macroinvertebrate responses to multiple environmental stressors is an important tool for water quality management, by predicting ecological effects of both stressors and restoration practices. Currently, existing modelling approaches fall short in simulating the responses of macroinvertebrate assemblages to environmental constraints, lacking incorporation of the multiple spatial and temporal scales on which stressors act, including their mutual interactions and uncertainties associated with input data. In answer to these shortcomings, this study aimed to design a conceptual multiscale model for simulating responses of macroinvertebrate assemblages to multiple environmental stressors. To this purpose, we drew up model requirements, selected model building blocks and assembled these into a conceptual model, also documenting the challenges that remain to be solved. This conceptual model offers a direction for simulating responses of macroinvertebrate assemblages to multiple stressors, which in turn can be used to better focus management resources and restoration practices.